2021
DOI: 10.1111/ppa.13334
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Erwinia sp. causing black rot of papaya (Carica papaya) first recorded in Okinawa Main Island, Japan

Abstract: Since 2002, papaya black rot has been spreading over several islands of Okinawa Prefecture, Japan. To devise a prevention strategy for the disease, microbiological research on the pathogen was conducted. Twelve strains were isolated from papaya infected with black rot showing symptoms such as water‐soaked lesions on stems and petioles, black spots on fruits, and rotted leaves turning yellow with necrotic spots. Through Koch's postulates, we confirmed that the isolated strains caused papaya black rot. Bacteriol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recently, E. mallotivora was reported to be affecting papaya in the Philippines and Indonesia, making this species a pathogen of concern that could affect the papaya industry in the entire Southeast Asia region [ 7 , 12 ]. A similar disease termed as papaya black rot has been recently detected in Japan and the pathogen was characterised to be from the genus Erwinia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, E. mallotivora was reported to be affecting papaya in the Philippines and Indonesia, making this species a pathogen of concern that could affect the papaya industry in the entire Southeast Asia region [ 7 , 12 ]. A similar disease termed as papaya black rot has been recently detected in Japan and the pathogen was characterised to be from the genus Erwinia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, a bacterium identi ed as Erwinia papayae was reported to cause 'papaya dieback' disease in Malaysia (Maktar et al, 2008). The 'crown rot' disease that was recently observed in the Philippines (dela Cueva et al, 2017) and 'black rot' disease in Japan (Hanagasaki et al, 2021) were both reported to be caused by Erwinia mallotivora. Interestingly, the 'crown rot' disease of papaya in the Republic of Tonga in Africa was reported to be caused also by E. mallotivora (Fullerton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, a bacterium identified as Erwinia papayae was reported to cause 'papaya dieback' disease in Malaysia (Maktar et al, 2008). The 'crown rot' disease that was recently observed in the Philippines (dela Cueva et al, 2017) and 'black rot' disease in Japan (Hanagasaki et al, 2020) were both reported to be caused by Erwinia mallotivora. Interestingly, the 'crown rot' disease of papaya in the Republic of Tonga in Africa was reported to be caused also by E. mallotivora (Fullerton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%